Alternative domestic rodent pest management approaches to address the hazardous use of metal phosphides in low- and middle-income countries - (:unkn) unknown (My University, 2024)
This article looks at the position of African student entrepreneurs in the implementation of migration control in Tunisia. At the crossroads of the migration and development worlds, “African students” have been a prime target for international migration government actors since 2015 and the arrival of significant European funds for migration management. Often aimed to “raise awareness” among people considered to be “migrants” of the risks of migration and the opportunities of entrepreneurial models in Africa, these actors have been able to develop success models based on access to and the promotion of mobility within the African continent. Against a purely opportunistic reading of migration control, this article seeks to understand how students’ involvement in the ordering of mobility connects to a pan-Africanist political imaginary.
Keywords: African Research